A rare combination of rare conditions: Salmonella septic sacroiliitis and hepatitis. (5th December 2012) - Penney, Nicholas; Konan, Sujith; Hulme, Alison
Abstract : We report an unusual presentation of sacroiliitis and hepatitis secondary to Salmonella systemic infection. A high index of suspicion, early blood cultures, prompt investigations and treatment with parenteral antibiotics can result in complete resolution of symptoms and prevent long-term sequelae of either condition.